Avaliação de vegetação monodominante do Pantanal e vegetação de Cerrado, utilizando parâmetros biofísicos estimados por imagens de satélites - Seixas, Guilherme Barros (2013)
This study aimed to determine the variability of biophysical parameters of rainfall and evapotranspiration in area Cambarazal and Cerrado, using Landsat and Terra satellite images and meteorological radar TRMM (Tropical Rainfall Measuring Mission). The study area is located in the subregion of Barão Melgaço Pantanal, Mato Grosso State, Brasil, inserted between the parallels 15 º and 17 º S and meridians 55 ° to 57 ° W, at an average altitude of 140 m. Three sub-areas were selected for collection of meteorological data: two in Cerrado, in Miranda Farm and Experimental Farm UFMT, both located in the municipality of Santo Antônio de Leverger - MT, and one in area Cambarazal in Particular Reserve of Patrimônio Natural (RPPN, Serviço Social do Comércio-Pantanal), in Barão de Melgaço-MT. The surface measurements were performed on micrometeorological towers and weather stations located in the study area and data were extracted from the National Water Agency and the National Institute of Meteorology. Rainfall data covering the study area were obtained from TRMM. We acquired images of products MOD11A2, MOD15A2, MOD16A2, MOD13Q1 originated from MODIS onboard Terra satellite and sensor images TM (Thematic Mapper) Landsat 5, for a clear sky days. Applying the first steps of the algorithm SEBAL -Surface Energy Balance Algorithm for Land, were mapped vegetation indices and surface temperature for the entire study area, with a resolution of 30 m. Rainfall estimated by TRMM revealed a strong correlation with the surface data and we found that the correlation increases with increasing time scale (MODIS product 3B43, r = 0,85). The vegetation indices obtained by MODIS revealed seasonality in both Cerrado and in Cambarazal. The IAF, obtained by light interception for the upper stratum of Cambarazal, was strongly correlated (r = 0,72) with LAI estimated by MODIS. The MODIS LAI showed a significant difference (p < 0.05) between Cerrado and Cambarazal, and the annual average for the Cerrado was 1,4  0,5 and for Cambarazal was 5,3  0,9 . The annual average value found for the NDVI was 0,58  0,09 and the EVI was 0,34  0,10 in the Cerrado. Cambarazal on the annual average value found for the NDVI was 0,82  0,04 and EVI was 0,47  0,07. The actual evapotranspiration data revealed that average annual water consumption Cambarazal was 66 % higher than the Cerrado. Average actual evapotranspiration was 25,2  10,7 mm 8dia-1 in the Cambarazal, while the Cerrado was 15,2  8,2 mm 8dia-1 for the entire study period.